Humoral response after the fourth dose of the SARS-CoV-2 vaccine in the CKD spectrum: a prespecified analysis of the SENCOVAC study. Issue 4 (24th November 2022) - Quiroga, Borja; Soler, María José; Ortiz, Alberto; Jarava Mantecón, Carlos Jesús; Gomes Pérez, Virginia Olinda; Bordils, Antoni; Lacueva, José; Marin Franco, Antonio José; Delgado Conde, Pablo; Muñoz Ramos, Patricia; Calderón González, Carmen; Cazorla López, Juan Manuel; et al.
ABSTRACT: Background: There is scarce evidence on the fourth dose of severe acute respiratory syndrome coronavirus 2 vaccines in chronic kidney disease (CKD) patients. We evaluated the humoral response and effectivity of the fourth dose in the CKD spectrum: non-dialysis CKD (ND-CKD), haemodialysis (HD), peritoneal dialysis (PD) and kidney transplant (KT) recipients. Methods: This is a prespecified analysis of the prospective, observational, multicentric SENCOVAC study. In patients with CKD who had received a complete initial vaccination and one or two boosters and had anti-Spike antibody determinations 6 and 12 months after the initial vaccination, we analysed factors associated with persistent negative humoral response and higher anti-Spike antibody titres as well as the efficacy of vaccination on coronavirus disease 2019 (COVID-19) severity. Results: Of 2186 patients (18% KT, 8% PD, 69% HD and 5% ND-CKD), 30% had received a fourth dose. The fourth dose increased anti-Spike antibody titres in HD ( P  = .001) and ND-CKD ( P  = .014) patients and seroconverted 72% of previously negative patients. Higher anti-Spike antibody titres at 12 months were independently associated with repeated exposure to antigen (fourth dose, previous breakthrough infections), previous anti-Spike antibody titres and not being a KT recipient. Breakthrough COVID-19 was registered in 137 (6%) patients, 5% of whom required admission. Admitted patients had prior titres <620 UI/ml and median values were lower ( P  = .020) than in non-admitted patients. Conclusions: A fourth vaccine dose increased anti-Spike antibody titres or seroconverted many CKD patients, but those with the highest need for a vaccine booster (i.e. those with lower pre-booster antibody titres or KT recipients) derived the least benefit in terms of antibody titres. Admission for breakthrough COVID-19 was associated with low anti-Spike antibody titres. Graphical Abstract: